"Oral" Tribological Study on the Astringency Sensation of Red Wines. Issue 5 (5th April 2016) - Brossard, Natalia; Cai, Huifang; Osorio, Fernando; Bordeu, Edmundo; Chen, Jianshe
Abstract: Astringency is a specific oral sensation dominated by a dryness and puckering feeling and is one of the main quality factors for red wines, teas as well as some fruit products. Various hypotheses have been proposed to explain the mechanisms of the astringency sensation; however which prevails is still unknown. Here we used a tribological system to determine if the astringency is predominantly a physical perception. Mixtures of whole human saliva and typical astringent compounds such as tannins and red wines were evaluated for their lubrication behavior. Friction coefficient was measured over a wide range of lubrication speed. By comparing friction coefficient with human sensory results of astringency, a positive correlation was found. In particular the highest correlation was observed ( R 2  = 0.93) at a sliding speed of 0.075 mm/s. Results from this work demonstrate that astringency of polyphenol‐rich products is a sensory perception via a physical stimulus and can be quantified using tribology techniques. Practical Applications: There is an increasing interest in sensory astringency, particularly its signaling process in oral cavity and the quantitative assessment of its intensity. This is due to the fact that astringency is an important quality characteristic which strongly influences consumer's acceptability for many polyphenol‐rich foods. This research achieved the first experimental approach to sensory astringency determination on red wines by using a tribological technique. Results from this work positively confirm the hypothesis that astringency is a tactile sensation. The method established in this work provides a useful tool for efficient determination of astringent intensity both as industrial quality control and for the prediction of consumer's sensory perception.